Evaluating the Moderating Role of Work-Life Balance on the Effect of Job Stress on Job Satisfaction - Melis Attar; Vural Çağlıyan; Aleem Abdul-Kareem (Istanbul Business Research (IBR), 2020)
Work has occupied an essential place in human life, and this has caused many employees to spend a substantial amount of their time at workplaces. The purpose of this study is to assess the moderating role of work-life balance on the effect of job stress on employees' job satisfaction. A survey method is used to collect the necessary data for this research. A total of 308 respondents from 90 manufacturing SMEs operating in Konya took part in the study. The data gathered are analyzed using SPSS 23 program and Hayes PROCESS macro v.3.4.1. The results of the analyses reveal a statistically significant negative effect of job stress and positive effect of work-life balance on job satisfaction. Moreover, work-life balance is found not to have a moderating role on the effect of job stress on job satisfaction. It is recommended that policy makers and managers of SMEs need to institute stress management techniques that have the propensity of reducing the negative consequences of job stress while maximizing its merits, as well as formulating strategies that will enable employees to have a balance between their personal and work lives.
Keywords: 650; Work-life balance; Job stress; Job satisfaction; Moderating role; SMEs